2016
DOI: 10.3906/tar-1509-57
|View full text |Cite
|
Sign up to set email alerts
|

Impact of passive modified atmosphere packaging on physicochemical properties, bioactive compounds, and quality attributes of sweet pomegranates

Abstract: In recent years, the production and consumption of pomegranate fruit is increasing rapidly throughout the world, mainly due to greater awareness of its nutritive and medicinal attributes. Pomegranates are rich sources of polyphenols, including ellagitannins, gallotannins, ellagic acids, gallagic acids, catechins, anthocyanins, ferulic acids, and quercetins. These polyphenols exhibit various biological activities, such as eliminating free radicals, inhibiting oxidation and microbial growth, and decreasing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
16
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
(76 reference statements)
13
16
2
2
Order By: Relevance
“…From the data available to date, it is observed that changes in total phenolics during the storage in MAP is much more contradictory due to factors such as nature of plant tissue and the composition of atmosphere in the package headspace. Similar to our results, several authors showed that total phenolic content and total anthocyanin content slightly decreased during the storage period in low O 2 and high CO 2 atmospheres of packages of pomegranate arils (Lopez-Rubira et al 2005;Palma et al 2009;Caleb et al 2013;Martinez-Romero et al 2013), and pomegranate fruit (Selc¸uk and Erkan 2016). For pomegranate arils, declining of total phenolic content or total anthocyanin content can be explained by transforming them in to brown polymers by the action of polyphenol oxidase (PPO) as also stated by Radziejewska-Kubzdela et al (2013), Darsana et al (2016), Singh et al (2013) and Shivashankar et al (2004).…”
Section: Weight Losssupporting
confidence: 91%
See 1 more Smart Citation
“…From the data available to date, it is observed that changes in total phenolics during the storage in MAP is much more contradictory due to factors such as nature of plant tissue and the composition of atmosphere in the package headspace. Similar to our results, several authors showed that total phenolic content and total anthocyanin content slightly decreased during the storage period in low O 2 and high CO 2 atmospheres of packages of pomegranate arils (Lopez-Rubira et al 2005;Palma et al 2009;Caleb et al 2013;Martinez-Romero et al 2013), and pomegranate fruit (Selc¸uk and Erkan 2016). For pomegranate arils, declining of total phenolic content or total anthocyanin content can be explained by transforming them in to brown polymers by the action of polyphenol oxidase (PPO) as also stated by Radziejewska-Kubzdela et al (2013), Darsana et al (2016), Singh et al (2013) and Shivashankar et al (2004).…”
Section: Weight Losssupporting
confidence: 91%
“…; Martinez‐Romero et al . ), and pomegranate fruit (Selçuk and Erkan ). For pomegranate arils, declining of total phenolic content or total anthocyanin content can be explained by transforming them in to brown polymers by the action of polyphenol oxidase (PPO) as also stated by Radziejewska‐Kubzdela et al .…”
Section: Resultsmentioning
confidence: 99%
“…First, juices were centrifuged, and the upper parts of the solutions were used directly for phytochemical analyses. Total polyphenol content was determined using the colorimetric reaction with Folin-Ciocalteu reagent (Selçuk and Erkan, 2016). Gallic acid was used as an external standard for the calibration curve, and the results were expressed as milligrams of gallic acid equivalent (mg GAE L -1 ) of fruit juice.…”
Section: Plant Materials and Experimental Treatmentsmentioning
confidence: 99%
“…In other words, MAP is used for extending the storage and shelf‐life period of fresh products by changing the O 2 and CO 2 composition surrounding the products. MAP may also prevent weight loss and shriveling by creating a higher relative humidity (RH) in the surrounding environment of the products . MAP for lettuce has been shown to reduce weight loss, shrinkage, and decay, to delay senescence, and to maintain postharvest quality of lettuce heads in different types of lettuce by several researchers .…”
Section: Introductionmentioning
confidence: 99%
“…MAP may also prevent weight loss and shriveling by creating a higher relative humidity (RH) in the surrounding environment of the products. [14][15][16] MAP for lettuce has been shown to reduce weight loss, shrinkage, and decay, to delay senescence, and to maintain postharvest quality of lettuce heads in different types of lettuce by several researchers. 17,18 Harvested lettuce heads are usually exposed to uncontrolled humidity conditions during marketing and MAP helps to maintain optimal product quality.…”
Section: Introductionmentioning
confidence: 99%